Reprogramming tumor-associated macrophages as a unique approach to target tumor immunotherapy - Khan, Safir Ullah; Khan, Munir Ullah; Azhar Ud Din, Muhammad; Khan, Ibrar Muhammad; Khan, Muhammad Imran; Bungau, Simona; Hassan, Syed Shams ul (Frontiers in Immunology, 2023)
In the last ten years, it has become increasingly clear that tumor-infiltrating myeloid cells drive not just carcinogenesis via cancer-related inflammatory processes, but also tumor development, invasion, and metastasis. Tumor-associated macrophages (TAMs) in particular are the most common kind of leucocyte in many malignancies and play a crucial role in establishing a favorable microenvironment for tumor cells. Tumor-associated macrophage (TAM) is vital as the primary immune cell subset in the tumor microenvironment (TME).In order to proliferate and spread to new locations, tumors need to be able to hide from the immune system by creating an immune-suppressive environment. Because of the existence of pro-tumoral TAMs, conventional therapies like chemotherapy and radiotherapy often fail to restrain cancer growth. These cells are also to blame for the failure of innovative immunotherapies premised on immune-checkpoint suppression. Understanding the series of metabolic changes and functional plasticity experienced by TAMs in the complex TME will help to use TAMs as a target for tumor immunotherapy and develop more effective tumor treatment strategies. This review summarizes the latest research on the TAMs functional status, metabolic changes and focuses on the targeted therapy in solid tumors.